Evaluating Options For The Regulation Of Payday Loans - Anderson, Michael H.; Jackson, Raymond (Journal of Applied Business Research, 2017)
This study discusses regulatory options that federal and state legislatures might consider for the payday loan industry. These options include outright prohibition; restricting the implicit annual percentage interest rate; limiting the amount per loan; limiting the number of concurrent loans; setting lower and upper limits on contract length; and defining the waiting period between loans. While other studies examining the payday loan industry have relied on user survey data or data from a specific lender, this study utilizes data collected by the administrative agent for all payday loan activity in several states, including Florida, Illinois, and Oklahoma. A comparison of key empirical results derived from the differing regulatory environments in these states provides guidance to those who consider imposing further regulation. The current regulatory constraints have resulted in a relatively low default rate, a high rate of loan denial, and a troubling industry reliance on the frequent borrower. An analytical framework is suggested for understanding the motivations of the low and high frequency borrowers.